Saccadic Adaptation in 10–41 Month-Old Children - Lemoine-Lardennois, Christelle; Alahyane, Nadia; Tailhefer, Coline; Collins, Thérèse; Fagard, Jacqueline; Doré-Mazars, Karine (Frontiers in Human Neuroscience, 2016)
When saccade amplitude becomes systematically inaccurate, adaptation mechanisms gradually decrease or increase it until accurate saccade targeting is recovered. Adaptive shortening and adaptive lengthening of saccade amplitude rely on separate mechanisms in adults. When these adaptation mechanisms emerge during development is poorly known except that adaptive shortening processes are functional in children above 8 years of age. Yet, saccades in infants are consistently inaccurate (hypometric) as if adaptation mechanisms were not fully functional in early childhood. Here, we tested reactive saccade adaptation in 10-41 month-old children compared to a group of 20-30 years-old adults. A visual target representing a cartoon character appeared at successive and unpredictable locations 10° apart on a computer screen. During the eye movement toward the target, it systematically stepped in the direction opposite to the saccade to induce an adaptive shortening of saccade amplitude (Experiment 1). In Experiment 2, the target stepped in the same direction as the ongoing saccade to induce an adaptive lengthening of saccade amplitude. In both backward and forward adaptation experiments, saccade adaptation was compared to a control condition where there was no intrasaccadic target step. Analysis of baseline performance revealed both longer saccade reaction times and hypometric saccades in children compared to adults. In both experiments, children on average showed gradual changes in saccade amplitude consistent with the systematic intrasaccadic target steps. Moreover, the amount of amplitude change was similar between children and adults for both backward and forward adaptation. Finally, adaptation abilities in our child group were not related to age. Overall the results suggest that the neural mechanisms underlying reactive saccade adaptation are in place early during development.